Students at Risk: Predisposing Factors, Warning Signs, and Treatment Plans - David L. Griffin Sr. (Educational Considerations, 1995)
The medical model of predisposing factors and warning signs can be applied to ongoing concerns of students who are at risk of failing at school and/or life.